(untitled) (Plant Tissue Culture and Biotechnology, 2023)
An efficient Agrobacterium-mediated genetic transformation protocol has been developed in the present investigation to integrate salinity tolerant gene pea DNA helicase (PDH45) in two peanut varieties, Dhaka-1 and BARI Chinabadam-8. Decapitated half-embryo explants of the above-mentioned varieties were also used to develop a transformation compatible in vitro regeneration system. MS medium supplemented with 5.0 mg/l BAP and 0.5 mg/l Kn showed maximum response for shoot induction in both varieties. Half strength of MS medium supplemented with 0.2 mg/l IBA showed better response towards root induction for both varieties. Genetic transformation experiments were performed using Agrobacterium strain LBA4404 containing pCAMBIA1301-PDH45 conferring reporter gus gene, hygromycin resistance hpt gene, and salinity tolerant gene pdh45. The transformation variables were optimized, OD600 1.4 with 45 minutes of incubation period, and three days of co-culture showed the best performance. The transformed shoots were selected using 30 mg/l hygromycin. The overall transformation frequency was very low, where 0.10% shoots of Dhaka-1 and 0.07% shoots of BARI Chinabadam-8 survived the selection pressure. The stable integration of the transgene in the transformed shoots was confirmed through PCR analysis. Plant Tissue Cult. & Biotech. 33(1): 37-46, 2023 (June)